Brain SPECT in patients with neuropsychiatric SLE : the additional value of semi-quantitative analysis - Khider, Mohamed Abdelrahman (Stellenbosch : University Stellenbosch, 2010)
Thesis (MScMedSc (Medical Imaging and Clinical Oncology. Nuclear Medicine))--University of Stellenbosch, 2010.